Crystal engineering of a zwitterionic drug to neutral cocrystals: a general solution for floxacins - Gunnam, Anilkumar; Suresh, Kuthuru; Ganduri, Ramesh; Nangia, Ashwini (Chemical Communications, 2016)
The transformation of zwitterionic Sparfloxacin (SPX) to the neutral form is achieved by cocrystallization. Neutral forms of drugs are important for higher membrane permeability, while zwitterions are more soluble in water. The twin advantages of higher solubility/dissolution rate and good stability of neutral SPX are achieved in a molecular cocrystal compared to its zwitterionic SPX hydrate. The amine-phenol supra-molecular synthon drives cocrystal formation, with the paraben ester acting as a "proton migrator'' for the ionic to neutral transformation.

Curcumin: pharmaceutical solids as a platform to improve solubility and bioavailability - Suresh, Kuthuru; Nangia, Ashwini (Crystengcomm, 2018)
Curcumin (CUR) is the prime curcuminoid in the Indian dietary spice turmeric, Curcuma longa, a plant of the Zingiberaceae family. CUR has promising and diverse therapeutic benefits, such as antioxidant, anti-inflammatory, antitumor, anti-hyperglycemic, antimalarial, antibacterial, and antiviral activity, including anti-Alzheimer's disease. However, CUR is yet to reach the status of a therapeutic drug candidate mainly because a standard solid dosage of curcumin suffers from poor oral bioavailability (0.05 g mL(-1), less than 1%). The reasons behind its low bioavailability include poor solubility (<8 g mL(-1) in water), low permeability and absorption, and rapid metabolism (short elimination half-life of <2 h). A successful CUR therapy requires an appropriate formulation system that will enhance the bioavailability and offer greater therapeutic efficacy. This review covers a comprehensive description of the CUR pharmaceutical solids, such as polymorphs, cocrystals, eutectics, and coamorphous solid-state forms with aim to determine ways to improve its physicochemical properties, including dissolution rate, solubility, physicochemical stability, mechanical strength, compressibility for tablet formation, and oral bioavailability. The cumulative publications in the past decade have forecast a bright future for development of an oral drug formulation of curcumin.

Curcumin-artemisinin coamorphous solid: Xenograft model preclinical study - Mannava, M. K. Chaitanya; Suresh, Kuthuru; Bommaka, Manish Kumar; Konga, Durga Bhavani; Nangia, Ashwini (Pharmaceutics, 2018)
Curcumin is a natural compound present in Indian spice turmeric. It has diverse pharmacological action but low oral solubility and bioavailability continue to limit its use as a drug. With the aim of improving the bioavailability of Curcumin (CUR), we evaluated Curcumin-Pyrogallol (CUR-PYR) cocrystal and Curcumin-Artemisinin (CUR-ART) coamorphous solid. Both of these solid forms exhibited superior dissolution and pharmacokinetic behavior compared to pure CUR, which is practically insoluble in water. CUR-ART coamorphous solid showed two fold higher bioavailability than CUR-PYR cocrystal (at 200 mg/kg oral dose). Moreover, in simulated gastric and intestinal fluids (SGF and SIF), CUR-ART is stable up to 3 and 12 h, respectively. In addition, CUR-PYR and CUR-ART showed no adverse effects in toxicology studies (10 times higher dose at 2000 mg/kg). CUR-ART showed higher therapeutic effect and inhibited approximately 62% of tumor growth at 100 mg/kg oral dosage of CUR in xenograft models, which is equal to the positive control drug, doxorubicin (2 mg/kg) by i.v. administration.